Adaptation of cancer cells from different entities to the MDM2 inhibitor nutlin-3 results in the emergence of p53-mutated multi-drug-resistant cancer cells - Michaelis, Martin; Rothweiler, F.; Barth, S.; Cinatl, J.; Rikxoort, M. van; Löschmann, N.; Voges, Y.; Breitling, R.; Deimling, Andreas von; Rödel, F.; Weber, Kristoffer; Fehse, Boris; et al. (Cell death & disease, 2011)
Six p53 wild-type cancer cell lines from infrequently p53-mutated entities (neuroblastoma, rhabdomyosarcoma, and melanoma) were continuously exposed to increasing concentrations of the murine double minute 2 inhibitor nutlin-3, resulting in the emergence of nutlin-3-resistant, p53-mutated sublines displaying a multi-drug resistance phenotype. Only 2 out of 28 sublines adapted to various cytotoxic drugs harboured p53 mutations. Nutlin-3-adapted UKF-NB-3 cells (UKF-NB-3rNutlin10 μM, harbouring a G245C mutation) were also radiation resistant. Analysis of UKF-NB-3 and UKF-NB-3rNutlin10 μM cells by RNA interference experiments and lentiviral transduction of wild-type p53 into p53-mutated UKF-NB-3rNutlin10 μM cells revealed that the loss of p53 function contributes to the multi-drug resistance of UKF-NB-3rNutlin10 μM cells. Bioinformatics PANTHER pathway analysis based on microarray measurements of mRNA abundance indicated a substantial overlap in the signalling pathways differentially regulated between UKF-NB-3rNutlin10 μM and UKF-NB-3 and between UKF-NB-3 and its cisplatin-, doxorubicin-, or vincristine-resistant sublines. Repeated nutlin-3 adaptation of neuroblastoma cells resulted in sublines harbouring various p53 mutations with high frequency. A p53 wild-type single cell-derived UKF-NB-3 clone was adapted to nutlin-3 in independent experiments. Eight out of ten resulting sublines were p53-mutated harbouring six different p53 mutations. This indicates that nutlin-3 induces de novo p53 mutations not initially present in the original cell population. Therefore, nutlin-3-treated cancer patients should be carefully monitored for the emergence of p53-mutated, multi-drug-resistant cells.